2020
DOI: 10.1177/0300891620964571
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and types of EGFR mutations in Moroccan patients with non–small cell lung cancer

Abstract: Background: Mutations in the epidermal growth factor receptor ( EGFR) gene are commonly observed in non-small cell lung cancer (NSCLC), particularly in adenocarcinoma histology. The frequency of EGFR mutations is ethnicity-dependent, with a higher proportion reported in Asian populations than Caucasian populations. There is a lack of data on these mutations in north Africa. Methods: Tumor specimens from Moroccan patients with NSCLC were collected from five pathology laboratories between November 2010 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
(48 reference statements)
1
12
2
Order By: Relevance
“…Regarding the “classic” mutations such as deletion in exon 19 and p.L858R, we found that 23.5% of our patients carried deletion in exon 19, which is in line with data from previous studies including those conducted on Tunisian patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the p.L858R was identified in only four patients (11.7%), confirming once again the particularity of our cohort.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the “classic” mutations such as deletion in exon 19 and p.L858R, we found that 23.5% of our patients carried deletion in exon 19, which is in line with data from previous studies including those conducted on Tunisian patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the p.L858R was identified in only four patients (11.7%), confirming once again the particularity of our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…A meta-analysis including Middle Eastern and African studies reported a prevalence of 21.2% of EGFR mutations, varying from 44% in Turkey to 21% in Morocco and 2.1% in Saudi Arabia [ 34 ]. In addition, two recent studies from Morocco and Algeria revealed EGFR mutation frequencies of 21.9%, and 39.6%, respectively [ 35 , 36 ]. Analysis of the EGFR TKI sensitivity mutations in Tunisian NSCLC patients showed variable frequencies, depending on the number of analyzed samples, the patient’s selection criteria (clinical and pathological), and the used mutational analysis technique.…”
Section: Discussionmentioning
confidence: 99%
“…The use of erlotinib or other tyrosine kinase inhibitors in advanced non-small cell lung cancer is recommended for EGFR-mutated subtypes(10), and is associated with improved survival. The rate of EGFR testing was 8.1% which remains low as compared to reports from other parts of Africa 13 , 14 . Despite the available evidence that EGFR TKI agents are associated with improved survival and quality of life among patients with EGFR-mutated NSCLC, access and cost of these medicines remain a key bottleneck.…”
Section: Discussioncontrasting
confidence: 61%
“…In Morocco, EGFR mutation prevalences ranged from 15.9% to 26.8%. 27 - 29 Details of EGFR mutation prevalences in the MENA region are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These articles were assessed for eligibility and 15 studies were selected for this review: 11 (73.3%) from the Middle East [16][17][18][19][20][21][22][23][24][25][26] and 4 (26.6%) in North Africa. [27][28][29][30] Original articles were identified from Jordan, 16 Iran, 17 Turkey, [18][19][20] Iraq, 22 Lebanon, [23][24][25] Morocco, [27][28][29] and Egypt. 30 A multicenter prospective study from the Levant (Lebanone, Syria, Palestine, Jordan, Iraq, and Egypt) 26 and a multisite retrospective study from the Gulf (Saudi Arabia, the United Arab Emirates and Qatar) were also identified and will be part of our analysis.…”
Section: Literature Researchmentioning
confidence: 99%